Analysis of the Shooting Ability of Futsal Extracurricular Students at Budi Murni 3 High School in Medan - Sinaga, Boy Fernando; Ibrahim, Ibrahim; Nehe, Revan Nando; Rahmat, Ali; Syafiq, Muhammad Nabil Shal; Ginting, Ega Akia Fadila Br; Kaban, Ika Oktarina Br; Husni, Muhammad Rizky; Ramadhan, Muhammad Taufiq; Situmorang, Michael; Purba, Ilham Ari Affandi; Habibi, M. Arya (Journal Coaching Education Sports, 2025)
The purpose of this study was to determine the level of futsal shooting skills of extracurricular students of SMA Budi Murni 3 Medan. This study was conducted at SMA Budi Murni 3 Medan, Medan City, North Sumatra Province. The method and type of research used in this study were quantitative descriptive. The population in this study were all 10 students of SMA Budi Murni 3 Medan's futsal extracurricular activities. The number of samples in this study was all 10 students who took part in the SMA Budi Murni 3 Medan extracurricular activities. obtained by total sampling technique. The research instrument for data collection with tests and measurements was the Futsal Shooting Accuracy Test. The study was conducted. The research time was carried out for approximately 1 month. In one week, two meetings were held every Monday and Wednesday at 16.00, the meetings were 8 times. To see the shooting ability, survey and test calculations were used. From the results of the test, the level of shooting ability of extracurricular futsal students at SMA Budi Murni 3 Medan was mostly in the sufficient category.